Targeted precursor addition to increase baked flavour in a low-acrylamide potato-based matrix. (1st March 2021) - Kocadağlı, Tolgahan; Methven, Lisa; Kant, Avinash; Parker, Jane K.
Highlights: An enhancement of baked flavour in a low-acrylamide potato-based snack was achieved. There was no concomitant increase in acrylamide. This was achieved by adding a synergistic combination of amino acids and precursors. Key precursors were 2, 3-pentanedione, Gly, Ala, Val, Leu, Ile and Met. Enhancement was confirmed using both sensory and instrumental (GC–MS) analysis. Abstract: The aim of this study was to increase the baked flavour of low-acrylamide potato products. Strecker aldehydes and pyrazines make an important contribution to the flavour of potato products and are formed alongside acrylamide in the Maillard reaction. However, the Maillard reaction can be directed in favour of aroma formation by selecting appropriate precursors and intermediates based on the fundamental chemistry involved. Selected precursors were added to potato dough prior to baking. Addition of glycine and alanine together doubled high impact pyrazines and addition of 2, 3-pentanedione or 3, 4-hexanedione also promoted the formation of key trisubstituted pyrazines. Quantitative descriptive profiling of sensory attributes indicated that baked flavour was increased most when both Strecker aldehydes and pyrazines were increased together. This work shows that it is possible to enhance baked flavour in low-acrylamide products by adding a specifically targeted combination of amino acids and key intermediates, without increasing acrylamide concentration.